Human Resource Management (HRM) Practices of the Banking Sector inBangladesh: A Study on Private Commercial Bank - Mustafi, Mohitul Ameen Ahmed; Rahman, Tanzia; Jahan, Nusrat (Asian Business Review, 2016)
The purpose of this study is to find out HRM practices on the private commercial banking sector in Bangladesh. The researches want to examine the human resources management practices in the field of banking sector. It evaluates and compares existing human resources management activities of the employee like; job analysis, human resource planning, talent acquisition, training &development, performance appraisal, compensation, and the industrial relation of nine selective commercial banks. For conducting this research, 100 bank employees are randomly selected from the seven different banks. And out of this 91 employees responses properly; the response rate is 91 percent. The questionnaire consists of individual questions on seven HRM dimensions. The questionnaires were developed by considering five point Liker scale. The collected data were analyzed by applying both descriptive and inferential statistical techniques such as factor analysis and structural equation model (SEM). The SEM results indicated that job analysis, human resource planning, training & development, compensation, and industrial relation significantly and positively associated with overall human resource practices in private commercial banking sectors in Bangladesh. JEL Classifications: M10; M12; M19